(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The way youth speak about the past can offer important clues to how they conceptualise and emotionally negotiate the present, specifically their sense of place in a changing world and the security of their future within it. This article considers the case of youth admitted to a university through a ‘bridging’ programme to reflect on dilemmas of identity and class mobility facing South African youth. Based on participant-observation, working with a world history curriculum designed for educationally disadvantaged students, the researcher illustrates how widelycirculating public discourses about race and history have infused the moral and generational pressures black students report to be a constant source of tension in their lives. Their social positioning on the cusp of upward social mobility in a nation characterised by persistent, racialised economic inequalities is experienced both as a privilege and a burden. Tensions between, on the one hand, a proclaimed loyalty to communitarian interests and identities and, on the other, a desire to showcase full participation in new cultures of consumer materialism are resolved through dichotomous ways of speaking about the past. In these narratives, “History” is the term utilised for speaking of a past of traumatic events, black victimisation and social legacies which must be overcome; “tradition” is a word invoked to empower a positive sense of continuity and to fix a seemingly more secure and generous location in the present. Both languages of the past offer narrative resources for students who are negotiating a rapidly changing national and global context.